The Main Difficulties of Translating English Collocations (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the main challenges in translating English collocations into Uzbek. It emphasizes how cultural and semantic differences complicate direct translation. The paper discusses issues such as idiomatic expressions, metaphorical language, syntactic structures, and the importance of contextual adaptation. Examples from both languages demonstrate how literal translation can result in meaning loss, requiring creativity, reconstruction, or functional equivalents. The article argues that successful translation of collocations demands not only linguistic but also cultural sensitivity and a flexible, innovative approach from the translator to ensure natural and meaningful renderings.